Commodification Of Education In Transactional Leadership [A Literature Review Study] - Sukandi, Pipin; Yelli Eka Sumadhinata (CV. AFDIFAL MAJU BERKAH, 2024)
Higher education is increasingly seen as a commodity that can be bought and sold in the global market. This phenomenon emerges along with the development of a culture of capitalism that penetrates into the academic realm. This research examines the role of transactional leadership in the commodification of higher education in Indonesia. Using a case study approach of literature review from various journals, this research investigates how transactional leadership practices contribute to the transformation of education into an economically fungible product. The research findings reveal that transactional leadership encourages the creation of a management system that is oriented towards financial gain. Students are viewed as consumers, while education becomes a service that must be sold competitively. Transactional leaders tend to adopt business strategies such as aggressive marketing, diversification of study programs, and exploitation of human resources to maximize institutional income. Furthermore, this study analyzes the impact of education commodification on learning quality, academic integrity, and the welfare of the academic community. The results show that commodification can sacrifice essential aspects of education, such as intellectual development, character building, and the pursuit of scientific truth, in order to pursue financial goals. This study concludes that transactional leadership has the potential to change the face of higher education into a pure business activity, with significant consequences for the quality and purpose of education itself. The findings make an important contribution to the discussion on the direction of higher education in Indonesia and the role of leadership in determining the values embraced by educational institutions.